Theoretical and simulation analysis on rock breaking mechanical properties of arc-shaped PDC bit. (November 2021) - Ju, Pei; Tian, Dongzhuang; Wang, Chuanliu; Tian, Hongjie
Abstract: In order to grasp the rock breaking mechanical characteristics of arc-shaped PDC bit, and guide the optimization design of bit structure, theoretical calculation models of cutting parameters of PDC cutters were established. Taking Φ 94 mm tri-wing arc-shaped PDC bit as an example, theoretical calculation results show that, with the increase of radial distance, the cutting area, cutting arc length and cutting force of cutters approximately increase first and then decrease; the maximum cutting force is concentrated on number 5 and 6 cutters, which makes these two cutters very easy to be damaged in advance. Based on this, a Φ 94 mm four-wing arc-shaped PDC bit was designed, and the maximum cutting force is distributed on number 4, 5, 6 and 7 cutters, also the force value is greatly reduced, which is beneficial to the uniform wear of the cutters. At the same time, numerical simulation and field test were carried out, simulation results are in good agreement with the theoretical calculation results, and the wear conditions of the cutters in the field test are basically consistent with the theoretical and simulation results, which indicate the reliability of the theoretical calculation and the simulation results.